An overview on the use of ultraviolet radiation to disinfect air and surfaces - Albertini, Roberto; Colucci, Maria Eugenia; Coluccia, Alessia; Mohieldin Mahgoub Ibrahim , Mostafa; Zoni, Roberta; Veronesi, Licia; Affanni, Paola; Pasquarella, Cesira (Acta Biomedica Atenei Parmensis, 2023)
Background and aim Ultraviolet radiation (UV) is the portion of the electromagnetic spectrum of wavelengths between 200 and 400 nm divided into three bands called UVA, UVB and UVC. Due its well-described antimicrobial activity, UVC can represent a useful tool for disinfect surfaces, water, and air. The aim of this study was to illustrate the studies over time ultraviolet germicidal irradiation (UVGI) to disinfect air and surfaces. Methods Articles on Scopus published until April 14, 2023, were considered. Many issues involving UV were deepened crosschecking with e.g., “air”, “surfaces”, “disinfection”, “bacteria”, “fungi”, “operating theatres”. According to the case, the following variables were considered: years and related number of articles, sources of publications, subject areas, type of document published, type of journal, nationalities of the authors. Results Since 30’s, 287 448 articles on UV have been published. Among UVGI, 22 159 articles covered bacteria issue, followed by fungi and viruses with about 12000 both. UVGI was addressed by 1941 and 931 articles for surfaces and air respectively. Of these, 122 were performed in operating theatres. Since 1987 works have been published on spacecraft and since 2000, on the use of UVGI robots for disinfect air and surfaces. Conclusions Our study shows the studies on UVGI and related issues. It also shows most recently perspectives about the applications e.g. during prolonged human-crewed missions on spacecrafts, to inactivate microorganisms in environments where the exchange of air is impossible.